PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Triyana Triyana; Indira Januarti (Diponegoro Journal of Accounting, 2026)
This study aims to test the effect of profitability, leverage, and company size on Corporate Social Responsibility disclosure. The variables used in the test are profitability, leverage, and company size as independent variables, with Corporate Social Responsibility disclosure as the dependent variable. The population in this study were manufacturing companies in the basic and chemical industries listed on the Indonesia Stock Exchange in 2020-2023. Sampling using the sensus sampling method with certain criteria resulted in 176 observation data for 4 years of research (2020-2023). The data analysis method used in this study is multiple linear regression analysis. The results of the study indicate that profitability has a positive effect on CSR disclosure, while leverage has no effect on CSR disclosure. Furthermore, company size doesn’t prove positive effect on CSR disclosure.